Evaluasi Pengelolaan Obat di Instalasi Farmasi Dinas Kesehatan Kota Surakarta Tahun 2015 - Ganet Eko Pramukantoro; Sunarti . (Jurnal Farmasi Indonesia, 2018)
Drug management is an important process in public health service. Inappropriate drugmanagement may exert negative effect on the quality of healthcare service in a District/City. Thepurpose of this study was to provide an overview and evaluation of drug supply managementthat includes: selection, procurement, distribution, and use in Pharmacy Installatio of SurakartaHealth Department.Data was collected retrospectively by tracing the documenst from previous years. Allprocess of selection, procurement, distribution, and usage were included. The obtained datawere evaluated and compared with the standard according to WHO and Ministry of Health(2010).Drug supply management in Pharmacy Department of Surakarta according to thestandards as follows : The availability of the drug as needed (102.84%), procurement ofessential drug (86.87%), procurement of generic drug (100%), drug availability compared toDOEN (60.22%) and planning accuracy (88.94%). Drug availability level (100%), drugdistribution appropriateness (29,41%), the number of drug distributed inappropriately (9,84%),and the avarage time of drug emptiness (0%). The accuracy level of drugs item with Fornas I(60,77%). Our study concluded that drug management in Pharmacy Installation of SurakartaHealth Office still need improvement especially on distribution and utilization process accordingto WHO and Ministry of Health (2010) standards.